Fine Mapping of Leishmania major Susceptibility Locus lmr2 and Evidence of a Role for Fli1 in Disease and Wound Healing - Sakthianandeswaren, Anuratha (American Society for Microbiology (ASM), 2010)
Genetic linkage studies of the host response to Leishmania major, the causative agent of cutaneous leishmaniasis, have identified significant genetic complexity in humans and mice. In the mouse model, multiple loci have been implicated in susceptibility to infection, but to date, the genes underlying these loci have not been identified. We now describe the contribution of a novel candidate gene, Fli1, to both L. major resistance and enhanced wound healing. We have previously mapped the L. major response locus, lmr2, to proximal chromosome 9 in a genetic cross between the resistant C57BL/6 strain and the susceptible BALB/c strain. We now show that the presence of the resistant C57BL/6 lmr2 allele in susceptible BALB/c mice confers an enhanced L. major resistance and wound healing phenotype. Fine mapping of the lmr2 locus permitted the localization of the lmr2 quantitative trait locus to a 5-Mb interval comprising 21 genes, of which microarray analysis was able to identify differential expression in 1 gene—Fli1. Analysis of Fli1 expression in wounded and L. major-infected skin and naïve and infected lymph nodes validated the importance of Fli1 in lesion resolution and wound healing and identified 3 polymorphisms in the Fli1 promoter, among which a GA repeat element may be the important contributor.